2020
DOI: 10.21203/rs.3.rs-24238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship of chronic endometritis with chronic deciduitis in cases of miscarriage.

Abstract: Background: The presence of chronic deciduitis (CD) was determined in patients diagnosed with or without chronic endometritis (CE) before pregnancy to study the effect of CE on decidua in cases of miscarriage.Methods: Decidual tissue was obtained from the patients who miscarried at the first pregnancy within a year after the diagnosis of the presence or absence of CE. The number and distribution pattern of plasma cells stained with CD138 in decidual tissue in 10 high-power fields (HPFs) was examined. The preva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We have recently reported that chronic deciduitis (CD) was found more frequently in miscarriage cases among CE patients than Non-CE patients. 34 CD is thought to be a type of continuous and subtle inflammation in the decidua during pregnancy. [35][36][37][38][39] Chronic infection of microorganisms with immune disorder has been implicated as the pathophysiology of CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that chronic deciduitis (CD) was found more frequently in miscarriage cases among CE patients than Non-CE patients. 34 CD is thought to be a type of continuous and subtle inflammation in the decidua during pregnancy. [35][36][37][38][39] Chronic infection of microorganisms with immune disorder has been implicated as the pathophysiology of CD.…”
Section: Discussionmentioning
confidence: 99%
“…these specimens were already included and analyzed in the previous study. 34 The microbiome itself and/or inflammatory cytokines induced by this bacterium may affect embryonic development and cause miscarriage. 35,36 However, CE reportedly modifies decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, it has recently been noted that CE is associated with unexplained infertility, impaired implantation, and miscarriage. [3][4][5][6][7] The microbiota are deeply involved in the etiology of CE, since the cure rate is high with antibiotics treatment, and the clinical outcomes of in vitro fertilization (IVF) are improved after the confirmation of its cure. 3 The response of the endometrium to the microbiota and/or the microbiota itself is thus considered to be closely associated with implantation failure and infertility.…”
Section: Introductionmentioning
confidence: 99%